Information literacy in the context of the 21st century university - Alonso-Arévalo, Julio; Saraiva, Rosa María (Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2020)
The content available on the Web and in digital media has fundamentally changed the dynamics of the operation and management of the library's mission, which in turn is leading to a shift in the professional responsibilities and skills of librarians, and the potential for training is appreciated as a major resource at a time when the library's mission and the librarian's role are being questioned. Thus, a librarian, more than a manager of books, videos and digital files, should be considered a key member of his/her community and of the relations with his/her environment, focusing his/her work on advice and learning, on transversal skills, due to his/her experience in the knowledge of methodologies, flows and channels of information; aspects that are of essential value in the new learning and research environment, especially in the higher education environment. The article systematizes the participation of the university library and the librarian as a stakeholder, and trusted partner in the new higher learning ecosystem through the tasks of training, advising and literacy in information skills of students and researchers in their institution.